Pengaruh Pemberian Infusa Tumbuhan Sarang Semut (Hydnophytum formicarum) Terhadap Gambaran Histologi Pankreas Pada Tikus (Rattus norvegicus) Diabetes Terinduksi Aloksan - Muspita Jeli, Mutiana; Nurul Makiyah, SN. (Majalah Kesehatan Pharmamedika, 2011)
Oxidative stress has been implicated in pathogenesis of diabetes mellitus. In addition to increased production of free radicals, antioxidant defense systems are disturbed in diabetes mellitus. As a result, oxidative stress may cause oxidative damage of B-cell pancreas. Hydnophytum formicarum consists of flavonoid which function as an antioxidant. So that, it necessary do research to know influences of H. formicarum infusion to pancreas histology image of alloxan-induced-diabetic. This research is an experimental with in vivo design. Research subjects were 30 male rats Sprague Dawley strain, in 3-4 months, weight ± 200 gram were divided into 6 groups : normal control, negative control, glibenklamid dosage 0,5 mg/kgBW, H. formicarum dosage 1,26 g/kgBW, H. formicarum dosage 2,52 g/kgBW, and H. formicarum dosage 5,04 g/kgBW. Rats were inducted by alloxan dosage 130 mg/kgBW. Glibenklamid and infusion of H. formicarum were given once per day for 14 days orally. On the 15th day all the rats were then killed to carry out the pancreas. The analysis data using oneway anova test and post hoc test (Tukey).The result revealed that giving of glibenclamide, infusion of H. formicarum dosage 1,26 g/kgBW, dosage 2,52 g/kgBW, and dosage 5,04 g/kgBW was able to increase the size of Langerhans islet and amount of β-cells. Based on that, the conlusion is infusion of H. formicarum could minimize the damage of pacreas of alloxan-induced diabetic image.